A new technique to detect loss of insulation life in power transformers - Abu Bakar, Norazhar Bin (Curtin University, 2016)
This thesis proposes an alternative method of measuring the IFT and dissolved gases in transformer oil using absorption spectroscopy which can be performed instantly on-site and potentially to be implemented on-line. A new fuzzy logic approach to provide a proper asset management decision and predict the remaining operational life of a power transformer based on routine insulating oil tests such as furan, DGA, IFT, water content, and operating temperature has been proposed in this thesis.